The Effect of Credit Risk and Liquidity Risk on Bank Profitability - Rahadiansyah, Reska Budi; Edwiga, Taqwa Ananda; Lestari, Henny Setyo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The purpose of this study was to determine the extent to which Credit risk, Liquid Assets to Deposit Ratio, and Bank Size to affect the profitability of banks listed on the Indonesia Stock Exchange during the period 2019 - 2023. The variables analyzed in this study, namely Credit risk, Liquidity risk, and Liquid Assets to Deposit Ratio, as well as control variables, namely Bank Size, GDP Growth, and Inflation. This study uses a panel data regression method with a random effect model approach to test the relationship between variables. The results showed that Credit risk has a significant negative effect on profitability, while Liquidity risk has no significant effect. Liquid Assets To Deposit Ratio and Bank Size have a positive effect on bank profitability. Meanwhile, GDP Growth and Inflation have no significant effect. These findings theoretically confirm that the importance of managing credit risk and liquidity risk in maintaining the financial performance of banks. The implications of this study provide direction for investors and banking management to make strategic decisions in risk assessment, liquidity structure, and growth policy to improve profitability and competitiveness in the banking sector.